Evaluation of the efficacy of sodium hypochlorite in sanitization of lettuce (Lactuca sativa) - Santos, Hugo de Sousa (2012)
(Lactuca sativa). Aiming this, it was analyzed twenty-eight samples of refrigerated lettuce obtained directly in a supermarket in the city of Teresina, State of Piauí. The samples were washed in flowing water and, subsequently, picked randomly to form four groups to be used in the immersion time treatment in bleach solution in 200 ppm of active chlorine: zero (control), 15, 30 and 45 minutes. Then, the microbiological analyses were made: enumeration of total coliforms, thermotolerant coliforms and Escherichia coli (EC); counting of mesophilic heterotrophic bacteria (HBC) and fungi (F). The bleach solution in 200 ppm of active chlorine reduces the initial microbial load of heterotrophic bacteria, thermotolerant coliforms and Escherichia coli in lettuce leaves after 15 minutes of immersion. However, it was not effective to reduce the ammount of total coliforms, filamentous fungi and yeasts. Therefore, the domestic use of bleach, recommended by charts distributed to Brazilian consumers, is not effective to rightly sanitize lettuce leaves infected by coliforms, fungi and Escherichia coli.